Pembangunan Aplikasi Penilaian Ujian Skripsi Berbasis Android Dengan Menggunakan Metode Prototyping (Studi Kasus : Fakultas Ilmu Komputer Universitas Brawijaya Malang) - Edwin Nurwansyah; Herman Tolle; Satrio Agung Wicaksono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Faculty of Computer Science is one of the faculty in Brawijaya University Malang which runs its business process using website based system. The system called FILKOM APPS has operated to handle the academic process. However, the existence of the system is still less than optimal and has not adjusted the needs of current users, namely the need for a mobile device-based system. Because users more often use mobile devices to use the system and when the user feels the display of this system is less to adjust the display on mobile devices, thus making the user difficulty in accessing the system through their mobile device. Therefore the need for systems that can run on mobile devices to match the needs of today's users. The development of mobile device-based systems uses a prototyping development cycle with an object-oriented approach. The development of this mobile device based system is only done on the android operating system and using the native mobile device development approach. The results obtained from this research in the form of design and implementation of the system that can adjust the needs of users today. In designing this system consists of activity diagrams, sequence diagrams, class diagrams and physical data model. Applications that are based on the design of the resulting application that runs well through validation and security testing.